Unintended consequences of people’s housing programme / Baharuddin Mat Asek - Mat Asek, Baharuddin (2010)
Housing policy in Malaysia is not much linked to other social policies that dealing with poverty reduction. The poverty issues are tackled by the government through sectoral, instead of issue based approach, thus making an integrated approach not feasible. Housing policy is supposed to fix the past mistakes and to have a better future. People’s Housing Programme (PHP) tried to solve urban housing problems but on the contrarily, it symbolized and stigmatized its dwellers. Policy wise, housing programmes should work with the market. However, due to discrepancies in selling price between PHP and market price, there are supply and equity implications. Buyers of PHP are better off because they buy at a much cheaper price. Instead of supplying housing directly, vouchers are better option; the government can target the poorest of the poor and be able to promote non-concentration objectives. The poor families can move into the private rental housing and to neighbourhoods of higher income. However, production subsidies instead of voucher need to be used in promoting neighbourhood redevelopment. Nevertheless, production subsidies may be used for the elderly, mentally and physically disable persons’ housing. PHP housing policy, with a “one size fits all” model does not work. People have different housing needs and priorities change through time. The regional solutions are pertinent, in this case states and local authorities must remove regulatory barriers. PHP implementation has the potential to reduce housing supply for the poor and low income groups. Furthermore, it discourages the state government’s involvement in housing planning and development.